Jordan Jobs Diagnostic - Winkler, Hernan; Gonzalez, Alvaro (World Bank, Washington, DC, 2019)
This report provides a detailed diagnostic of the Jordanian labor market. It finds that labor market outcomes are worsening in Jordan. It has one of the lowest levels of labor force participation in the world, and only one out of every three working-age Jordanians has a job. Low rates of firm entry and exit suggest that the process of creative destruction is limited. Most private sector firms are either small – and stay small or large and old. The share of employment in small firms -which tend to be less productive- is growing. Employment is increasingly informal, less productive. High levels of informality drive down overall levels of labor productivity and suggests that important distortions affect the allocation of resources in the economy. At the same time, a large inflow of Syrian refugees and economic migrants makes the need for job creation even more urgent.